Effects of a cholecystokinin receptor antagonist on intestinal phase of pancreatic and biliary responses in man. - Hildebrand, P (1990)
The present study was designed (a) to characterize the activity of loxiglumide as a peripheral cholecystokinin (CCK) antagonist in healthy human subjects, and (b) to determine whether CCK is a physiologic regulator of the intestinal phase of meal-stimulated exocrine pancreatic and biliary secretions in man. Intravenous loxiglumide (22 mumol/kg per h) was highly potent in antagonizing CCK8-induced pancreatic enzyme and bile acid secretion as well as pancreatic polypeptide release. The potency and selectivity of loxiglumide as an antagonist of CCK provides the tool for evaluating the role of CCK as a physiological mediator of meal-induced pancreatic and biliary responses in humans. Infusion of a liquid test meal into the duodenum evoked an immediate response of pancreatic enzyme and bilirubin outputs, respectively. Intravenous loxiglumide significantly inhibited the meal-induced pancreatic amylase output by 63% (P less than 0.05), lipase output by 43% (P less than 0.05), and bilirubin output by 59% (P less than 0.05). These data suggest that CCK is a physiological mediator of the intestinal phase of meal-stimulated pancreatic and biliary responses.